SEMANTIC FIELDS IN PROVERBS: A CROSS LINGUISTIC STUDY OF MORAL CONCEPTS - Kambarova Marjan Adil kizi (Web of Journals Publishing, 2026)
This article deals with such moral concepts as honesty and truth, hard work and diligence, justice and fairness as well as respect for elders and experience in English and Russian proverbs. It demonstrates how both traditions use proverbs to convey moral values, but with notable cultural differences in emphasis and framing. English proverbs tend to present virtues such as honesty, hard work, and justice in pragmatic, rational, and outcome-oriented terms, highlighting personal responsibility, efficiency, and intellectual reasoning. Russian proverbs, by contrast, emphasize the ethical, communal, and moral dimensions of these values, framing honesty, diligence, fairness, and respect for elders as obligations that strengthen social cohesion and moral integrity. The analysis reveals that despite these cultural differences, both English and Russian proverbial traditions affirm universal moral principles, reflecting shared human concerns about ethical conduct, social order, and personal development.
Keywords: Proverb, moral concepts, honesty and justice, hard work and diligence, justice and fairness, respect for elders and experience.